Identification of optimum operatives parameters for Pulse Nd:YAG laser in paint removal on different types of car coated substrate - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman; Syahrul Affandi Saidi (2014)
The optimum operatives parameters of Cynosure Cynergy Pulse Nd:YAG laser in paint removal process has been identified on three types of car coated substrate samples A, B and C with the coating thicknesses ranging from 92 – 134 μm, 196 – 450 μm and 219 – 283 μm respectively. Alicona IFM G4 analysis was done on 540 irradiated craters in obtaining the depth thickness (d) between the crater surface level and top coating surface level for average coating removal efficiency (ϵ) determination. FESEM and EDX analysis were done to reveal the physical and chemical characteristics of best selected crater depth accounted from the highest ϵ obtained. In this study, the optimum operatives process for sample A is set-up with pulse width (PW) 100 ms, repetition rate (RR) 1.0 Hz and beam size (BS) 5 mm at F 180 J/cm2 . The optimum operative process for Sample B is set up with PW 200 ms, RR 1.0 Hz, BS 5 mm at F 220 J/cm2 whereas the optimum operative process for sample C is set-up with PW 100 ms, RR 2.0 Hz, BS 5 mm at F 150 J/cm2 .